2015
DOI: 10.1155/2015/169015
|View full text |Cite
|
Sign up to set email alerts
|

Simulations Based on Experimental Data of the Behaviour of a Monocrystalline Silicon Photovoltaic Module

Abstract: The performance of monocrystalline silicon cells depends widely on the parameters like the series and shunt resistances, the diode reverse saturation current, and the ideality factor. Many authors consider these parameters as constant while others determine their values based on the -characteristic when the module is under illumination or in the dark. This paper presents a new method for extracting the series resistance, the diode reverse saturation current, and the ideality factor. The proposed extraction met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…(i) From 0 to 50 s, irradiance is at 755 W/m 2 (high), SOC is at 25% (low), and grid voltage is at 220 V (present). Sbnet is open (0), Sbpv is closed (1), and the PV array is charging the batteries; (ii) From 50 to 100 s, irradiance is at 825 W/m 2 (high), SOC is at 80% (medium), and grid voltage is at 220 V (present…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…(i) From 0 to 50 s, irradiance is at 755 W/m 2 (high), SOC is at 25% (low), and grid voltage is at 220 V (present). Sbnet is open (0), Sbpv is closed (1), and the PV array is charging the batteries; (ii) From 50 to 100 s, irradiance is at 825 W/m 2 (high), SOC is at 80% (medium), and grid voltage is at 220 V (present…”
Section: Data Availabilitymentioning
confidence: 99%
“…Te aspect of electric power in everyday requirements of the population cannot be exaggerated, especially in this era of spreading of consumer electronics and electrical appliances for both home and industrial use. Te need is quite evident on an ever-increasing demand [1,2]. Te period of the inconsistency of supply electricity is long forgotten in many developed countries of the world while developing countries still writhe holdups arising from persistent power failure.…”
Section: Introductionmentioning
confidence: 99%
“…The correct design, calibration, and use of these sophisticated equipment provide good information about the irradiance at a given location [16,17]. On the other hand, many papers aimed at improving the prediction of the performance of a PV energy capture system have been published [14,[18][19][20][21][22][23]. From an adequate analysis of direct solar measurements and the predicted response of the PV systems it is possible to calculate the energy obtainable for a given location [24,25].…”
Section: Journal Of Solar Energymentioning
confidence: 99%
“…Concerning the extracted parameters issued from the numerous analytical methods, our review of literature has shown that they are generally expressed with respect to the data related to the three via points when they are decoupled but for some methods they are also related to one or more other parameters (Ibrahim & Anani;2017;Ndegwa et al, 2020). It has also shown that there are many theoretical and some experimental studies dedicated to analyzing the influence of the extracted parameters on different quantities such as the current, voltage, temperature, illumination and to some data related to the three points (Bashahu & Nkundabakura, 2007;Dandoussou et al, 2015;El Tayyan, 2015;Singh & Ravindra, 2011;Venkateswari & Rajasekar, 2021). On the other hand, very few experimental studies can be found that highlight the interdependency between parameters such as the series resistance and the ideality factor (Park et al, 2018;Rana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%